Práticas sustentáveis em restaurantes universitários de Universidades Federais Brasileiras - Ferraz, Thanísia Valim (2016)
Universities must use sustainable measures in their routines, since they are also great consumers of goods and generators of waste, they present the social function of disseminating knowledge, helping in the formation of a more balanced society and in the stimulus of sustainable development. In this context we have the University Restaurants, which due to their activities consume water and energy resources and generate a large amount of waste. Therefore, the present study sought to carry out a survey of sustainable practices in University Restaurants of the Brazilian Federal Universities by sending an electronic questionnaire. After analyzing the results it was observed that among the sustainable practices we have: (i) reuse of oil and fats, (ii) selective collection and recycling, (iii) campaigns against food waste, (iv) rational use of water and energy resources, (v) the use of utensils of permanent materials, (vi) the acquisition of fruits and vegetables without the addition of pesticides or family farming, (vii) satisfaction surveys and (viii) the seasonality of fruits and vegetables. The results show that there is a concern with the sustainability of the University Restaurants and that the awareness of the whole academic community is fundamental to the success of the implementation and continuity of sustainable practices in the University Restaurants